PERSEPSI PENYAKIT SEBAGAI PREDIKTOR DEPRESI PADA ORANG DEWASA DENGAN PENYAKIT KRONIS DI PURWOKERTO, JAWA TENGAH, INDONESIA - Rahajeng Win Martani; Sunanta Thongpat; Suparpit Von Boorman (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2017)
Depression is common mental disorder that found in adults with chronic illness. Thenumber of depression among adults with chronic illness is increasing worldwideand particularly inIndonesia. Therefore, studies have shown strong associations between illness perception, illnessuncertainty, and depression; but the different findings of studies investigating the effect ofindividual characteristics. The findings of this study will be useful as supporting data for localhealth care providers to develop future intervention programs and to design new strategies toreduce depression and to promote well-being among adults with chronic illness.This study wasdesigned to identify illness perception in predicting depressionamong adults with chronic illness inPurwokerto, Central Java, Indonesia. A descriptive study with cross sectional design was usedwith total sample 283adults with chronic illness, aged from 36 until 59 years old were required.Multi-stage random sampling was used in Public Health Centers of Purwokerto. Brief IllnessPerception Questionnaire (BIPQ) was used as the instrument in this study. Logistic Regressionanalysis was used for analyzed data. The result revealed that 53.7% respondents have poorperception related to their illness and 46.3% have good illness perception. Illness perception wassignificantly found as predictor of depression among adults with chronic illness in Purwokerto,Central Java Indonesia with Neglekerke R square .114 and p –value .000.